Модель оцiнювання якостi емоцiйної регуляцiї професiйної дiяльностi працiвникiв за умови роботи з пiдвищеною небезпекою - Кальниш, В.В.; Стасишин, Р.О.; Оліскевич, М.О. (Кибернетика и вычислительная техника, 2017)
Розроблено концепцію моделювання, засновану на застосуванні багатофакторної регресійної пробіт моделі. Це дозволяє оцінювати вірогідність ризику погіршення якості емоційної регуляції для конкретного працівника на основі інформації про його емоційний стан. Статистично значущий вплив на ризик погіршення емоційного стану працівника мають характеристики відчуття сили і енергії, імпульсивної реактивності та рівня психічної депресії. Підвищення імпульсивної реактивності працівника зумовлює збільшення ризику критичного погіршення якості емоційної регуляції. Встановлено, що вплив цього чинника є сильнішим в порівнянні з впливом рівня психічної депресії. Показано, що приналежність до різних вікових груп не є суттєвим фактором, який впливає на ризик погіршення якості емоційної регуляції слюсарів оперативно-виїзних бригад на підприємствах електроенергетичної галузі. Разработана концепция моделирования, основанная на применении многофакторной регрессионной пробит модели. Это позволяет оценивать вероятность риска ухудшения качества эмоциональной регуляции для каждого конкретного работника на основе информации о его эмоциональном состоянии. Статистически значимое влияние на риск ухудшения эмоционального состояния работника оказывают характеристики ощущения силы и энергии, импульсивной реактивности и уровня психической депрессии. Повышение импульсивной реактивности работника приводит к увеличению риска критического ухудшения качества эмоциональной регуляции, причем влияние этого фактора более выражено по сравнению с влиянием уровня психической депрессии. Показано, что принадлежность к разным возрастным группам не является существенным фактором, влияющим на риск ухудшения качества эмоциональной регуляции слесарей оперативно-выездных бригад. Introduction. There are a number of occupations in Ukraine, including electric power industry occupations, where people work in high-risk conditions. These conditions impose on the workers a significant amount of restrictions on their functions and professionally important qualities, which leads to the emergence of certain requirements in the process of professional selection and monitoring. One of the main requirements to the staff in potentially dangerous objects is the high level of readiness to work in difficult situations. This implies the presence of relevant professional qualities among the employees of these occupations, one of the most important is emotional stability, which closely links with the maintenance of work ability and attention in the conditions of responsible work accomplishing. The purpose of the article is to develop an approach for quantifying the deviation from the "proper" level of emotional regulation and to identify on this basis the structure of the relevant reactions distribution for locksmiths of operational-outgoing brigades at electric power industry. Methods. The survey of workers was conducted by means of SOPAS-8 method, which was adapted for a comprehensive study of the individual mental stability to the extreme activity factors impact. According to this method, eight factors of the mental state were identified: mental rest, feeling of satisfaction; strength and energy sensitivity; desire for action; impulsive reactivity; mental depression and exhaustion feeling; depressed mood; mental anxiety or indignation, stress; anxiety and fear feeling. Materials of psycho-physiological observations were analyzed using methods of variation statistics, multivariate analysis, regression binary models. Results. A modeling concept based on the multi-factor regression probit model was developed. Developed approach allows to estimate the risk of a deterioration in the quality of emotional regulation for each individual employee based on information about the factors observed values for his emotional state regardless of age. Conclusions. The statistically significant influence on the risk of an employee's emotional state deterioration create the characteristics of strength and energy sensitivity, impulsive reactivity, mental depression and exhaustion feeling levels. Our investigation revealed that belonging to different age groups is not a significant factor to affect the risk of deterioration in the emotional regulation quality for electricians at operational-outgoing brigades.